Effect of Bone Marrow-Derived Mesenchymal Stem Cells on Endotoxin-Induced Oxidation of Plasma Cysteine and Glutathione in Mice - Smita S. Iyer; Edilson Torres-Gonzalez; David C. Neujahr; Mike Kwon; Kenneth L. Brigham; Dean P. Jones; Ana L. Mora; Mauricio Rojas (Stem Cells International)
Bone marrow-derived mesenchymal stem cells (BMDMSC) are emerging as a therapeutic modality in various inflammatory disease states, including acute lung injury (ALI). A hallmark of inflammation, and a consistent observation in patients with ALI, is a perturbation in the systemic redox environment. However, little is known about the effects of BMDMSC on the systemic redox status. The objective of the present study was to determine whether exogenously infused BMDMSC protect against endotoxin-induced oxidation of plasma cysteine (Cys) and glutathione (GSH) redox states. To determine the effect on the redox state if BMDMSC, mice received endotoxin intraperitoneally (1 mg/kg), followed by intravenous infusion of either 5×105 BMDMSC or an equal volume of saline solution. Control mice received intraperitoneal endotoxin followed by 5×105 lung fibroblasts given intravenously. Cys, cystine (CySS), GSH, and glutathione disulfide (GSSG) concentrations were determined by HPLC. Results showed sequential preservation of plasma Cys and GSH levels in response to BMDMSC infusion. The data show that BMDMSC infusion leads to a more reducing Cys and GSH redox state. The findings are the first to demonstrate that BMDMSC have antioxidant effects in vivo, and add to our understanding of the systemic effects of BMDMSC in lung injury.